Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan Remaja dalam Pencegahan Penyalahgunaan NAPZA di SMA Katolik St. Petrus Kanisius Palangka Raya: Effects of Health Education on Adolescent Knowledge Levels in Drugs Abuse Prevention in St. Catholic High School Petrus Kanisius Palangka Raya - Carolina, Putria; Tarigan, Yelstria Ulina (Jurnal Surya Medika (JSM), 2019)
Narcotics, psychotropic substances and addictive substances (NAPZA) are substances or drugs derived from plants or not synthetic or semisynthetic plants that can cause a decrease or change in consciousness, loss of taste, reduce pain relief, and can create dependence, which is differentiated into in groups as attached in the Republic of Indonesia Law Number 35 of 2009. Data from the National Narcotics Agency in Central Kalimantan in 2015, it was known that the number of rehabilitated drug users with 15-20 years of age was 46 people (13.9%) out of 330 people (BNNP Central Kalimantan, 2015). The purpose of this study was to find out whether there was an effect of the provision of health education on the level of knowledge of adolescents in preventing drug abuse in Catholic High School St. Petrus Kanisius, Palangka Raya City. This study uses a type of pre-experimental research with a one group pre-post test approach with the Wilcoxon test. The population in this study were Catholic High School St. Petrus Kanisius, Palangka Raya City totaling 47 students, using simple random sampling. Through the results of the analysis in this study obtained the value of Z for knowledge that is -5,514a with P Value Asymp.Sig. (2-tailed) Knowledge of 0,000 which means it is smaller than a = 0.05, so it is concluded P Value ≤ 0.05, then Ha is accepted. This means that there is an influence of health education on the level of knowledge of adolescents in preventing drug abuse in Catholic High School St. Petrus Kanisius, Palangka Raya City. Suggestions for health workers based on the results of this study should be able to increase the role of educators in increasing knowledge which is expected to be the basis for behavior changes in adolescents so that they do not use illegal drugs that harm health.